Sorting by interfacial tension (SIFT): label-free selection of live cells based on single-cell metabolism. Issue 8 (8th March 2019) - Pan, Ching W.; Horvath, Daniel G.; Braza, Samuel; Moore, Trevor; Lynch, Annabella; Feit, Cameron; Abbyad, Paul
Abstract : A new label-free and passive microfluidic technique to select cells based on single-cell glycolytic activity. The method has broad applicability and we demonstrate here single-cell droplet encapsulation and selection of live cells. Abstract : Selection of live cells from a population is critical in many biological studies and biotechnologies. We present here a novel droplet microfluidic approach that allows for label-free and passive selection of live cells using the glycolytic activity of individual cells. It was observed that with the use of a specific surfactant utilized to stabilize droplet formation, the interfacial tension of droplets was very sensitive to pH. After incubation, cellular lactate release results in droplets containing a live cell to attain a lower pH than other droplets. This enables the sorting of droplets containing live cells when confined droplets flow over a microfabricated trench oriented diagonally with respect to the direction of flow. The technique is demonstrated with human U87 glioblastoma cells for the selection of only droplets containing a live cell while excluding either empty droplets or droplets containing a dead cell. This label-free sorting method, dubbed sorting by interfacial tension (SIFT) presents a new strategy to sort diverse cell types based on metabolic activity.